DOKTER DETEKTIF’S KEY OPINION LEADER EFFECT ON THE INTENTION PURCHASE OF SKINCARE PRODUCTS - Pasaribu, Sisra Yeni; Anggraini, Tania; Apriyana, Nurliya (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2025)
Abstract: The development of digital technology impacted business and marketing strategies on social media. Using a Key Opinion Leader (KOL) was one of the business and marketing strategies using the name of the key opinion leader to attract the consumer's intention to buy a product. Dokter Detektif is one of the KOLs for the skin care category. She reviewed skin care products, particularly the consistency between company claims and laboratory test results. The study aimed to see the impact of Dokter Detektif's key opinion leader on purchase intention for skincare products. This research was a quantitative study using purposive sampling techniques with 100 respondents. This study used non-probability sampling for data collection. The population of this study is skincare consumers, social media users, aged 18-45, and knowledgeable about Dokter Detektif. The variables in this study were familiarity, trustworthiness, expertise, and purchase intention. The results showed that Dokter Detektif's familiarity, trustworthiness, and expertise have a significant correlation to affect the intention of consumers to purchase skin care products. This research concluded that skincare entrepreneurs must ensure that the composition of skin care products matches the results of laboratory tests to receive a good rating from a Dokter Detektif.